Growth mechanism, structure and thermoelectric properties of thermally evaporated Bi₂(Te₀,₉Se₀.₁)₃ thin films - Rogacheva, E. I.; Krivonogov, S. I.; Fedorov, A. G.; Sipatov, A. Yu.; Doroshenko, A. N.; Nashchekina, O. N.; Novak, K. V. (State Scientific Institution "Institute for Single Crystals", 2022)
The growth mechanism, crystal structure, and morphology of thin films with thicknesses d = 16-207 nm prepared by thermal evaporation in vacuum of p-Bi2(Te0.9Se0.1)3 polycrystal on glass substrates were studied using X-ray diffractometry and atomic force microscopy. The obtained polycrystalline thin films were single-phase and homogeneous, had a tetradymite-type structure and a unit cell parameter very close to that of Bi2(Te0.9Se0.1)3 polycrystal but, unlike the initial polycrystal, exhibited n-type conductivity. With increasing d, the grain size and roughness of the thin films increased. It was found that the predominant direction of the crystallite growth was [0 0 l], but at d larger than ~ 130 nm, along with the reflections from the (0 0 l) planes, weak reflections from other planes appeared, indicating a certain disorientation of crystallites. An increase in d led to a monotonic increase in the Seebeck coefficient, which indicated the presence of the classical size effect. The obtained data have shown that using a low-cost method of thermal evaporation in vacuum from a single source, one can grow thin Bi2(Te0.9Se0.1)3 films with partial Te -> Se substitution in Bi2Te3 of a sufficiently high quality with preferential orientation [0 0 l].
Механізм росту, структура та термоелектричні властивості термічно випарених тонких плівок
Keywords: Bi₂(Te₀,₉Se₀.₁)₃; polycrystal; thermal evaporation; thin film; thickness; phase composition; crystal structure; microstructure; growth direction; Seebeck coefficient